Polycomb complexes and the propagation of the methylation mark at the Drosophila Ubx gene. - Kahn, T.G.; Schwartz, Y.B.; Dellino, G.I.; Pirrotta, V. (Journal of Biological Chemistry, 2006)
Polycomb group proteins are transcriptional repressors that control many developmental genes. The Polycomb group protein Enhancer of Zeste has been shown in vitro to methylate specifically lysine 27 and lysine 9 of histone H3 but the role of this modification in Polycomb silencing is unknown. We show that H3 trimethylated at lysine 27 is found on the entire Ubx gene silenced by Polycomb. However, Enhancer of Zeste and other Polycomb group proteins stay primarily localized at their response elements, which appear to be the least methylated parts of the silenced gene. Our results suggest that, contrary to the prevailing view, the Polycomb group proteins and methyltransferase complexes are recruited to the Polycomb response elements independently of histone methylation and then loop over to scan the entire region, methylating all accessible nucleosomes. We propose that the Polycomb chromodomain is required for the looping mechanism that spreads methylation over a broad domain, which in turn is required for the stability of the Polycomb group protein complex. Both the spread of methylation from the Polycomb response elements, and the silencing effect can be blocked by the gypsy insulator.